2009
DOI: 10.1364/ol.34.002667
|View full text |Cite
|
Sign up to set email alerts
|

Critically coupled surface phonon-polariton excitation in silicon carbide

Abstract: We observe critical coupling to surface phonon-polaritons in silicon carbide by attenuated total reflection of mid-IR radiation. Reflectance measurements demonstrate critical coupling by a double scan of wavelength and incidence angle. Critical coupling occurs when prism coupling loss is equal to losses in silicon carbide and the substrate, resulting in maximal electric field enhancement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 12 publications
0
52
0
Order By: Relevance
“…However, we stress that interesting materials such as restrahlen crystals [66] exist in the mid-infrared region. We have also seen that many interesting concepts relating to linear and nonlinear metamaterials can be tested and implemented in the microwave region.…”
Section: Transformation Optics Across the Spectrummentioning
confidence: 86%
“…However, we stress that interesting materials such as restrahlen crystals [66] exist in the mid-infrared region. We have also seen that many interesting concepts relating to linear and nonlinear metamaterials can be tested and implemented in the microwave region.…”
Section: Transformation Optics Across the Spectrummentioning
confidence: 86%
“…The two guided TM modes can be interpreted as a result of hybridization between two surface phonon-polaritons supported by the individual SiC/vacuum interfaces [25].…”
Section: Electromagnetic Properties Of the Swabsicmentioning
confidence: 99%
“…The quantity Q res determines the fill time of the structure according to T fill % ðQ res =2Þ! À1 if the following two simplifying assumptions are made: (i) beam-loading Q beam ¼ Q res , and (ii) the structure is critically coupled [25]. Based on the properties of the luminous L-modes, only modest values of Q res $ 500-1000 are expected, which translates into T fill $ 1:5 ps-3:0 ps.…”
Section: ðYþ ¼ Ementioning
confidence: 99%
“…Surface phonon-polartions (SPPs) have been recently proposed [1][2][3] as potential energy carriers to enhance significantly the phonon heat transport in polar nanomaterials with low thermal conductivity, as is the case of the amorphous SiO 2 and crystalline SiC. Many theoretical [4][5][6][7] and experimental [8,9] studies have shown that the propagation length of SPPs traveling along the interface of nanofilms can be more than three orders of magnitude larger than the corresponding phonon mean free path, which yields in turn a SPP thermal conductivity comparable or higher than the phonon counterpart.…”
Section: Introductionmentioning
confidence: 99%